2013
DOI: 10.5187/jast.2013.55.6.521
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Multiple Connexins in Rat Corpus and Cauda Epididymis at Various Postnatal Stages

Abstract: Direct cell-cell communication via the transfer of small molecules between neighboring cells in tissue is accomplished by gap junctions composed of various connexins (Cxs). Proper postnatal development of the epididymis is important for acquisition of male reproduction. The epididymal epithelium is composed of several cell types, and some of these cells are connected by gap junctions. The present study was conducted to determine the presence of Cx transcripts in the corpus and cauda epididymis. In addition, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 24 publications
4
14
0
Order By: Relevance
“…Especially, this research shows expressional change of Cx 43 in the caudal epididymis, but not in the corpus epididymis (Lydka et al, 2011). As seen in our previous (Lee, 2013 & 2015) and present researches, Cx 43 is the most predominant form of Cx isoforms in the epididymis. Thus, it is important to notice the opposite effects of high-dose EB and low-dose flutamide treatments on expression of Cx 43 in the corpus and caudal epididymis.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Especially, this research shows expressional change of Cx 43 in the caudal epididymis, but not in the corpus epididymis (Lydka et al, 2011). As seen in our previous (Lee, 2013 & 2015) and present researches, Cx 43 is the most predominant form of Cx isoforms in the epididymis. Thus, it is important to notice the opposite effects of high-dose EB and low-dose flutamide treatments on expression of Cx 43 in the corpus and caudal epididymis.…”
Section: Discussionsupporting
confidence: 85%
“…The presence and expression of tissue-specific Cx isoforms have been determined by several researches (Goodengough et al, 1996; Willecke et al, 2002). The differential expression of Cx isoforms in the epididymis during postnatal period has been demonstrated by our previous and other researches (Dufresne et al, 2003; Han & Lee, 2013; Lee 2013; Pointis et al, 2005). Moreover, our recent findings have demonstrated that expression of Cx isoforms in the initial segment and corpus epididymis is differentially regulated by estradiol benzoate, an agonist of estradiol, or flutamide, a synthetic antiandrogen, which is administrated at the early neonatal and/or weaning age (Lee, 2014; Lee & Lee, 2015).…”
Section: Introductionsupporting
confidence: 64%
“…Expression of several Cx isoforms has been found in many types of mammalian tissues and even a specific cell type (Goodenough & Paul, 2009). In case of the epididymis, the presence and expression of 8 to 9 different Cx isoforms have been identified from our earlier researches and others (Cry, 2011; Lee, 2013; Seo et al, 2010). Also, the expression of Cx isoforms in the epididymis is segmental specific and/or postnatal development age-specific (Lee, 2013; Seo et al, 2010).…”
Section: Introductionsupporting
confidence: 56%
“…In case of the epididymis, the presence and expression of 8 to 9 different Cx isoforms have been identified from our earlier researches and others (Cry, 2011; Lee, 2013; Seo et al, 2010). Also, the expression of Cx isoforms in the epididymis is segmental specific and/or postnatal development age-specific (Lee, 2013; Seo et al, 2010). Even though Cry et al (1996) has demonstrated the presence of Cx 43 in the base of the epithelium between basal and principal cells in the rat epididymis, little information is available for the localization of other Cx isoforms in the epididymis.…”
Section: Introductionsupporting
confidence: 56%
“…More than 20 Cx isoforms in mammals have been identified up to date (Meşe et al, 2007). Several researches have demonstrated the presence of Cxs in the male reproductive tract (Cry, 2011;Lee, 2013;Seo et al, 2010). Segment-specific expression of Cxs in the epididymis during postnatal development has been reported .…”
Section: Introductionmentioning
confidence: 99%